Spectroscopic properties of the dwarf nova-type cataclysmic variables observed by LAMOST. (13th July 2020) - Han, Zhongtao; Boonrucksar, Soonthornthum; Qian, Shengbang; Xiaohui, Fang; Wang, Qishan; Zhu, Liying; Dong, Aijun; Zhi, Qijun
Abstract: Spectra of 76 known dwarf novae from the LAMOST survey were presented. Most of the objects were observed in quiescence, and about 16 systems have typical outburst spectra. 36 of these systems were observed by SDSS, and most of their spectra are similar to the SDSS spectra. Two objects, V367 Peg and V537 Peg, are the first spectra of the object. The spectrum of V367 Peg shows a contribution from an M-type donor and its spectral type could be estimated as M3-5 by combining its orbital period. The signature of a white dwarf spectrum can be seen clearly in four low-accretion-rate WZ Sge stars. Other special spectral features worthy of further observations are also noted and discussed. We present a LAMOST spectral atlas of outbursting dwarf novae. Six objects have their first outburst spectra given here, and the others were also compared with the published outburst spectra. We argue that these data will be useful for further investigation of the accretion disc properties. The He ii λ4686 emission line can be found in the outburst spectra of seven dwarf novae. These objects are excellent candidates for probing the spiral asymmetries of accretion disc.